PENENTUAN JARAK AMAN PELEDAKAN BATUBARA TERHADAP LINGKUNGAN SEKITAR WILAYAH PERTAMBANGAN - Rachmat Hidayat; Bambang Joko Priatmadi; Meldia Septiana; Dini Sofarini (Universitas Lambung Mangkurat, 2014)
Mineral mining activities in Indonesia, especially those conducted in the open pit, to dismantle the hard rock is usually done by blasting. Blasting process is often conducted over the protests of the residents of the villages around the mining area , due to frequent ground shaking (ground vibration ) whose velocity exceeds the threshold value at certain distances from the center of the ground shaking explosions cause damage and discomfort felt by surrounding population . Based on this, the research was conducted to determine the safe distance from the blasting vibration of the ground (ground vibration) and air blast (air blast) criteria based on the value of the safety standards that blasting can be well designed and to determine a safe zone for blasting activities. This study uses data processing BlastMate III / Minimate Plus is recorded into the computer/laptop using software blastware. The recorded data is then analyzed by comparing these data with existing vibration standards. The results of the study on coal blasting vibration will use Standard Quality Decree No. LH. 49 of 1996 . The results showed a safe distance from the blasting vibration ground (ground vibration) in the village of Manggis sub district Kelumpang is as far as 1037.84 meters upstream from the point of explosive or active pit areas with the use of blasting and air blast (air blast) is safe for the environment is at a distance comfort 900 m from the blast point average into the borehole 15 m and average load of 40,000 kg of explosives. Minister of Environment Decree No. 49 of 1996 on Raw Vibration Level around the mining area suitable for blasting in the area of PT. Arutmin Tambang Senakin.